Steroids Produced by Endophytic Fungus Lasiodiplodia Theobromae From Aglaia Argentea Blume and Their Cytotoxic Activity Against Hela Cervical Cancer Cell Lines - Supratman, Unang; Purbaya, Sari; Harneti, Desi; Wulandari, Asri Peni; Mulyani, Yeni; Azhari, Azmi; Sari, Aprilia Permata (Molekul, 2023)
Three steroids, ergosterol (1), ergosterol peroxide (2) and stigmasterol (3) have been isolated from endophytic fungus, Lasiodiplodia theobromae derived from the root of Aglaia argentea Blume. The steroids were isolated by vacuum chromatography and column chromatography, the chemical structure was established following the analysis of 1D-NMR, 2D-NMR, IR, MS and by comparison with previously reported spectra data. Ergosterol peroxide (2) and stigmasterol (3) were reported for the first time isolated from Lasiodiplodia theobromae endophytic fungus. Cytotoxic activities of the compounds were tested with resazurin assay against HeLa cervical cancer cells, compound 2 displayed strongest cytotoxic activities against HeLa cervical cancer cells with IC50 values of 0.28 µM, while compounds 1 and 3 showed IC50 values of 0.34 µM and 27.32 µM, respectively